Jejunal villous atrophy with morbid obesity: death after jejunoileal bypass. Issue 11 (November 1982) - Logan, R F; Ferguson, A
Abstract : A 49-year-old woman with morbid obesity was found to have subtotal villous atrophy in an operative jejunal biopsy, taken when a jejunoileal bypass was created. After the operation, the patient developed marked weight loss, vomiting, hepatic failure, and a bizarre mental state with sudden losses of consciousness. Six months after the first operation the bypass was reversed but the patient developed hepatorenal failure and died one week after the second operation. The histological features of several biopsies of jejunum were typical of a gluten sensitive enteropathy. This, previously subclinical, small bowel disease may have contributed to her hepatic failure and death by interfering with jejunoileal adaptation. In the absence of any of the other, rarer, causes of villous atrophy, this woman appears to have had coeliac disease.